Model Rehabilitasi Anak Pelaku Kekerasan Seksual Pasca Undang-undang No. 12 Tahun 2022 Berdasarkan Prinsip Kepentingan Terbaik Bagi Anak - Nabilah, Eva Albatun; P, Berthi Ramadhani (Esensi Hukum, 2025)
This study aims to examine the extent to which the implementation of rehabilitation for Children in Conflict with the Law (CICL) in cases of sexual violence aligns with the principle of the best interests of the child following the enactment of Law No. 12 of 2022 on Sexual Violence Crimes, as well as to identify an appropriate implementation model to ensure alignment with the best interests of the child in the future.This research is a normative legal study with a descriptive approach. The data used in this research are secondary data obtained from literature studies. The secondary data consist of primary, secondary, and tertiary legal materials. The data analysis in this study employs a qualitative analysis method.The study finds that the rehabilitation of Children in Conflict with the Law in cases of sexual violence has not fully met the principle of the best interests of the child due to the absence of regulations that accommodate specific rehabilitation measures for children involved in such cases. The failure to fulfill this principle is not the fault of the implementing institutions but rather the result of a lack of regulatory frameworks that provide for specialized rehabilitation for children in cases of sexual violence.To ensure that rehabilitation for Children in Conflict with the Law in cases of sexual violence aligns with the principle of the best interests of the child in the future and to minimize the risk of recidivism, assessments must be conducted by professional teams who consider the child’s specific circumstances. Rehabilitation should be tailored to the child's special needs, include rehabilitation programs for the family, be supported by clear regulations that guide the rehabilitation model, and be implemented by human resources who possess a strong understanding of children's rights and needs. Keywords: Rehabilitation, Children in Conflict with the Law, Sexual Violence, Best Interests of the Child